A Critical Analysis of Monolingual and Bilingual Pupils’ Ability to Predict Outcome and Comprehend Sentences in a Reading Comprehension - Monday, Janet S.; Ekanem, Inibehe E. (Advances in Social Sciences Research Journal, 2023)
This study was carried out to analyze the monolingual and bilingual pupils’ ability to predict outcome and comprehend sentences in a reading comprehension passage. The research design adopted for the study was Quasi-experimental design. The study was conducted in Uyo, Akwa Ibom State. The population of the study comprised all 5,074 primary schools. The sample size that was used for the study consisted of 127, drawn from primary 3 pupils from 4 private primary schools in Uyo Senatorial District. The main instrument used for data collection in the study was titled “Performance of Monolingual and Bilingual Pupils” (PMBP). To ensure face and content validity of the instrument, the PMBP was given to the researcher’s supervisor and four experts (two in the Department of Early Childhood Education and two in English Department, all in the University of Uyo). In order to ensure the reliability of the research instrument, the PMBP was trial-tested on 30 private primary school children who were not part of the study, but the respondents have similar characteristics with those in the study area. The research questions 1-2 were answered using mean and standard deviation statistics, while the null hypotheses 1-2 were analyzed using Analysis of Covariance (ANCOVA). Decisions on the 2 null hypotheses were taken at .05 level of significance. The study concluded that monolingual and bilingual pupils do not differ significantly in their ability to predict outcome and comprehend sentences in reading comprehension passage. One of the recommendations made was that government, through effective monitoring, should ensure that all private schools teach the vernacular as a subject to their pupils as stipulated in the National Policy on Education for effective implementation.